Physical parameters affecting transient GUS gene expression in oil palm (Elaeis guineensis Jacq.) using the biolistic device - Parveez, Ghulam Kadir A.; Chowdhury, M.K.U.; M. Saleh, Norihan (Elsevier, 1997)
Physical parameters for DNA delivery into oil palm embryogenic calli using the biolistic device have been successfully established. Helium pressures, distance from rupture disc to macrocarrier, distance from macrocarrier to stopping plate, distance from stopping plate to target tissue, vacuum pressures, number of bombardments, particle types and sizes and the effect of calcium chloride and spermidine on microcarrier-DNA binding have been optimizied. Embryogenic calli were bombarded with gold or tungsten particles coated with pEmuGN plasmid containing β-glucuronidase gene (uidA) driven by an Emu promoter. A completely randomized design was used to bombard a total of 200 plates (40 parameters x 5 replications) which were then incubated in a growth chamber at 28°C. Two days after bombardment, the tissues were stained with GUS assay buffer for 16-20 h at 37°C and the blue spots were counted under a binocular microscope. Analysis of variance (ANOVA) and Duncan's new multiple range test were used to analyze data from each experiment. All the variables used in this experiment were significantly different except for vacuum pressures and bombardment numbers.